Polymorphous sweat gland carcinoma: a report of two cases. (5th April 2016) - Walker, Addie; Mesinkovska, Natasha A.; Emanuel, Patrick O.; Vidimos, Allison; Billings, Steven D.
Abstract : Polymorphous sweat gland carcinoma (PSGC) is a rare adnexal neoplasm with characteristic variegated histopathologic findings and low‐grade clinical behavior. First described in 1994, only 11 cases have been reported in the literature. It is named for the multiplicity of architectural patterns that may be present: solid, tubular, trabecular, pseudopapillary and cylindromatous. Owing to the multiple architectural patterns, the differential diagnosis is broad, including metastatic adenocarcinoma and other adnexal neoplasms with ductular differentiation. We present two new cases of PSGC and review the literature on this rare tumor.